2019
DOI: 10.3390/ani9030075
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Mechanisms of Small Ruminants to Environmental Heat Stress

Abstract: Small ruminants are the critical source of livelihood for rural people to the development of sustainable and environmentally sound production systems. They provided a source of meat, milk, skin, and fiber. The several contributions of small ruminants to the economy of millions of rural people are however being challenged by extreme heat stress difficulties. Heat stress is one of the most detrimental factors contributing to reduced growth, production, reproduction performance, milk quantity and quality, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 46 publications
2
92
0
8
Order By: Relevance
“…The number of mature individuals is estimated to be between 2000 and 5000 in the Kruger National Park (Ferreira et al, 2013). The geographical separation of the three national parks from which the warthogs were sampled, could have created small and fragmented subpopulations leading to escalated F IS values (Lamsyah et al, 2009) rs80854994 4 106,719,032 BCL2L15 Mastitis (Chen et al, 2015) Villages and DUR rs81282695 6 94,442,844 POU3F1 Neurobehavioral functioning (Eusebi et al, 2018) rs81282695 6 94442844 FHL3 Carcass traits (Zuo et al, 2004(Zuo et al, , 2007 Villages and KOL rs81430450 11 24,063,007 DNAJC15 Feeding efficiency (Reyer et al, 2017a) rs81430450 11 24,063,007 EPSTI1 Fertility traits (Gaddis et al, 2016), fat deposition (Zhang et al, 2018) SAL&LWT (Luo et al, 2012); carcass weight (Kang et al, 2013) Villages and WBO rs81244815 2 50,167,007 SWAP70 Disease resistance (Ma et al, 2011;Zhang et al, 2018) rs81244815 2 50,167,007 SBF2 Fertility (Zhang et al, 2014); immune function (Ibeagha-Awemu et al, 2016) rs81401075 8 73,841,435 FRAS1 Sow reproductive traits (Fischer et al, 2015), feed efficiency (Messad et al, 2019) rs81401075 8 73,841,435 NPY2R Obesity (Siddiq et al, 2007;Hunt et al, 2011) Villages (Smith et al, 2019); body width in gilts and sows (Rothschild, 2010), body weight traits (Borowska et al, 2017), altitude (Zhang et al, 2014) rs81478390 13 53,707,241 RYBP Body conformation traits -body weight, body length, body height, and chest circumference (Zhou et al, 2016) rs81330369 9 7,449,894 FCHSD2 Milk production traits (Kemper et al, 2015) rs80975991 7 33,481,446 ZFAND3 Growth and carcass quality traits (Li and Kim, 2015) rs80855522 4 11,0552,282 GNAI3 Heat tolerance (Berihulay et al, 2019) rs80988392 1 213,780,848 PTPRD Meat quality (Raschetti et al, 2013) due to Wahlund effect. As expected, we found that the village pig populations of South Africa had high inbreeding values compared with other popul...…”
Section: Discussionmentioning
confidence: 99%
“…The number of mature individuals is estimated to be between 2000 and 5000 in the Kruger National Park (Ferreira et al, 2013). The geographical separation of the three national parks from which the warthogs were sampled, could have created small and fragmented subpopulations leading to escalated F IS values (Lamsyah et al, 2009) rs80854994 4 106,719,032 BCL2L15 Mastitis (Chen et al, 2015) Villages and DUR rs81282695 6 94,442,844 POU3F1 Neurobehavioral functioning (Eusebi et al, 2018) rs81282695 6 94442844 FHL3 Carcass traits (Zuo et al, 2004(Zuo et al, , 2007 Villages and KOL rs81430450 11 24,063,007 DNAJC15 Feeding efficiency (Reyer et al, 2017a) rs81430450 11 24,063,007 EPSTI1 Fertility traits (Gaddis et al, 2016), fat deposition (Zhang et al, 2018) SAL&LWT (Luo et al, 2012); carcass weight (Kang et al, 2013) Villages and WBO rs81244815 2 50,167,007 SWAP70 Disease resistance (Ma et al, 2011;Zhang et al, 2018) rs81244815 2 50,167,007 SBF2 Fertility (Zhang et al, 2014); immune function (Ibeagha-Awemu et al, 2016) rs81401075 8 73,841,435 FRAS1 Sow reproductive traits (Fischer et al, 2015), feed efficiency (Messad et al, 2019) rs81401075 8 73,841,435 NPY2R Obesity (Siddiq et al, 2007;Hunt et al, 2011) Villages (Smith et al, 2019); body width in gilts and sows (Rothschild, 2010), body weight traits (Borowska et al, 2017), altitude (Zhang et al, 2014) rs81478390 13 53,707,241 RYBP Body conformation traits -body weight, body length, body height, and chest circumference (Zhou et al, 2016) rs81330369 9 7,449,894 FCHSD2 Milk production traits (Kemper et al, 2015) rs80975991 7 33,481,446 ZFAND3 Growth and carcass quality traits (Li and Kim, 2015) rs80855522 4 11,0552,282 GNAI3 Heat tolerance (Berihulay et al, 2019) rs80988392 1 213,780,848 PTPRD Meat quality (Raschetti et al, 2013) due to Wahlund effect. As expected, we found that the village pig populations of South Africa had high inbreeding values compared with other popul...…”
Section: Discussionmentioning
confidence: 99%
“…Goats ( Capra hircus ) play an important and critical role in the communities’ livelihood in arid and semi-arid regions in addition to their contribution to human food security by producing milk and meat, and for providing leader and manure as a fertilizer [ 1 , 2 ]. Therefore, goats are recommended livestock in tropics with minimal maintenance and low water requirements [ 3 5 ]. The total population of goats in Sudan is estimated to be 31.44 million heads [ 6 ], which are mainly distributed in all agro-ecological zones from arid Northern regions to humid Southern Sudan.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this high temperature and humidity environment, sheep will try to reduce their body temperature through their skin and breathing. Less comfortable environment due to high temperatures and humidity also causes sheep to reduce their food consumption yet increase their water drinking consumption (Berihulay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sheep are essential small ruminant resources in the tropics where they play a major role in sustaining poor family livelihood, especially in rural areas (Prabhu et al, 2009;Okoruwa, 2014;Berihulay et al, 2019). Sheep are less prone to hot environments than other ruminant animals (Bakheit et al, 2017).…”
Section: Introductionmentioning
confidence: 99%